The Effect Of Leverage, Inventory Intensity, Sales Growth, And Management Compensation On Tax Avoidance - Debby Berliana; Ratna Septiyanti (Cita konsultindo, 2024)
The research conducted between 2019 and 2023 examines how leverage, inventory levels, sales growth, and CEO compensation influence tax avoidance in consumer goods companies listed on the Indonesia Stock Exchange (IDX). The study utilizes descriptive statistics, classical hypothesis testing, and multiple regression analysis to analyze secondary data sourced from annual reports and financial statements. The findings suggest that leverage has no major influence on tax evasion, which contradicts earlier studies. Higher inventory levels are found to significantly decrease tax avoidance, implying that increased inventory may enhance taxable income. Sales growth is positively associated with tax avoidance, consistent with agency theory, which posits that rising profits encourage more tax avoidance. However, executive compensation does not appear to significantly affect tax avoidance, suggesting that the current compensation models in Indonesia might not be effective in driving tax avoidance behavior.